2021
DOI: 10.1177/00219983211041761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of process parameters on mode-II interlaminar fracture toughness and fractographic features of automated fibre placement prepreg laminates

Abstract: The present study concerns the quantitive assessment of the influence of process parameters on the interlaminar properties of carbon fiber reinforced epoxy composites. Mode II interlaminar fracture toughness is evaluated based on the ENF test. Scanning electron microscopy images are used to evaluate the change in microstructures. The results indicate that the process parameters have a direct influence on the microstructural features and fracture toughness of laminates. Specifically, the elevation of layup spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Compaction pressure is one of the most important process parameters regarding the final product quality [5]. Khan et al found that higher compaction pressures lead to a better overall quality of the laminate but can also result in high pressure air inclusions that lead to deconsolidation if the material is not cooled below glass transition temperature under the compaction roller [6].…”
Section: Compaction Roller Overviewmentioning
confidence: 99%
“…Compaction pressure is one of the most important process parameters regarding the final product quality [5]. Khan et al found that higher compaction pressures lead to a better overall quality of the laminate but can also result in high pressure air inclusions that lead to deconsolidation if the material is not cooled below glass transition temperature under the compaction roller [6].…”
Section: Compaction Roller Overviewmentioning
confidence: 99%
“…4,5 Therefore, the low interlaminar fracture toughness of composite materials has become a bottleneck for their engineering applications, seriously restricting the application of composite materials in the main bearing structures of aircraft. 6,7 To overcome the disadvantages of composite laminates, such as poor mechanical properties in the thickness direction, poor interlaminar properties, and a low ability to carry impact damage, researchers invented various translaminar reinforced (TLR) technologies, such as Z-pinning, 8 3D weaving, 9,10 stitching, 11 tufting, 12 and others. Z-pinning is not only a simple process with low requirements for production equipment and low costs but also has a low impact on the intralaminar property of the laminate.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Therefore, the low interlaminar fracture toughness of composite materials has become a bottleneck for their engineering applications, seriously restricting the application of composite materials in the main bearing structures of aircraft. 6,7…”
Section: Introductionmentioning
confidence: 99%